Evaluation of Power Quality of Wind Turbines for AL Maqrun city in Libya - Albohli, Nafaa; Elosta, Wedad (IJRDO-Journal of Applied Science, 2016)
RACTThe operation of wind turbines has animpact on the power quality of the electrical grid.The term power quality refers to voltage stability,frequency stability, and the absence of variousforms of electrical noise (e.g., flicker andharmonic distortion) on the electrical grid. Thepower quality will vary from location to location,depending on the nature of the wind resource, theturbine/generator technology used, and thecondition of the local electrical grid. The powerwill fluctuate due to wind speed variations. Powerfluctuation is affected by the number of windturbines and power control technology (pitch andstall regulation).It is important to study power fluctuationsin order to reduce these fluctuations that couldaffect electrical networks, and therefore to choosea proper wind turbine. Power fluctuations fromwind turbine generators can be predicted usingtwo methodologies. The first method is theturbulence intensity in the power output of windturbines, and the second method uses statisticaldata to analyze power output of wind turbines.In this paper the above mentionedparameters are studied through a statistical modelusing the above two methodologies. Wind datafor AL Maqrun city in Libya was used for theanalysis. This data was of ten minutes average forthe year 2003.The results show that using two windturbines instead of one turbine will improve thepower quality. Similar results are noticed for pitchcontrolled against stall controlled.The results were compared with resultsavailable in the literature showing a goodagreement.